The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0080-62342011000400002
|View full text |Cite
|
Sign up to set email alerts
|

Biografias de gravidez e maternidade na adolescência em assentamentos rurais no Rio Grande do Sul

Abstract: RESUMOBuscou-se conhecer e compreender as vivências de gestação e maternidade na adolescência em assentamentos rurais. O estudo desenvolveu-se a partir de uma abordagem qualitativa, sustentando-se no método biográfico. As testemunhas foram mulheres que vivenciaram gravidez e maternidade na adolescência. A coleta de dados foi realizada em Janeiro e Fevereiro de 2009, por meio de entrevista biográfica temática. As biografias mostram trajetórias familiares de instabilidade e mudanças constantes, além de habitação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
1
5
0
6
Order By: Relevance
“…A study [8] performed with adolescents showed that almost 100% of them had no job, but most of the interviewees have such desire, similar to the present research. This dream is about the expectation of independence and access to a better life from a material point of view.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A study [8] performed with adolescents showed that almost 100% of them had no job, but most of the interviewees have such desire, similar to the present research. This dream is about the expectation of independence and access to a better life from a material point of view.…”
Section: Discussionsupporting
confidence: 88%
“…Life perspectives refer to the anticipation in the present of future goals, representing the way in which the individual perceives and plans his/her future or life goals, being influenced by some theoretical factors such as professional maturity and motivation of the individuals given the life, socioeconomic factors, income and living with other cultures [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, foi evidenciado que as dificuldades iniciais de aceitação da maternidade na adolescência são gradualmente substituídas por maior aceitação e apoio, especialmente por parte da mãe da jovem 35 . Nesse sentido, empreende-se que há maior aceitação da gravidez e da criança pela família e, portanto, o estabelecimento de relações familiares mais positivas, quando as jovens possuem maior maturidade fisiológica e emocional, estabilidade conjugal e independên-cia financeira, condições essas mais prováveis de ocorrer entre as jovens mais velhas, mesmo que não concomitantemente 36 .…”
Section: Discussionunclassified
“…Lack of knowledge on the reproductive physiology and the consequences of sex intercourses observed in these situations are factors which result in pregnancy of adolescents, something which may compromise the growing of children and generate interruption of studies. 12,13 Most adolescents interrupts their school training at the time when pregnancy is discovered or they have already left school activities due to previous pregnancies, something which negatively interferes with their lifestyle, with adverse consequences on their prospects for study, work, and professional evolution. [14][15][16] This study is similar to other researches with regard to the marital status at the time of getting pregnant, which highlight that most adolescents were already living with their partners or husbands, something which seems to be a positive factor in face of pregnancy, where family ties get strengthened.…”
Section: -10mentioning
confidence: 99%